Development of an Android-Based Digital Room Service Module Called “Servino” at Vocational Schools Specializing in Culinary Arts - Angelina Mayoga Echa Wahyudi; Lucia Tri Pangesti; Niken Purwidiani; Febriani Lukitasari (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Room Service learning in Culinary vocational education requires learning media that is easily accessible and supports independent study. Due to its procedural nature, Room Service material demands an interactive and flexible presentation. This study aims to: (1) develop an Android-based Room Service digital module; (2) assess its feasibility in terms of content; (3) assess its feasibility in terms of media; and (4) analyze student responses to the module. This Research and Development (R&D) study utilizes the ADDIE model. Data were collected through questionnaires distributed to content experts, media experts, and Culinary students, and then analyzed using quantitative descriptive techniques. The results indicate that: (1) the Android-based Room Service digital module was successfully developed and is accessible via https://digitalstudio.my.id/p11/; (2) content feasibility reached a score of 94% (Very Feasible); (3) media feasibility reached 98% (Very Feasible); and (4) the average student response was 94% (Excellent). The SERVINO application was developed using iSpring Suite and Web2APK Builder, incorporating the Guided Note Taking learning method for structured note-keeping. These findings demonstrate that the SERVINO application serves as an effective digital solution to overcome internet connectivity barriers in schools while enhancing students' procedural mastery through offline-accessible demonstrations. This research contributes to the digital transformation of vocational pedagogy by providing a practical mobile-based model for culinary training.